Impact of COVID-19 on Cardiovascular Disease Presentation, Emergency Department Triage and Inpatient Cardiology Services in a Low- to Middle-Income Country - Perspective from a Tertiary Care Hospital of Pakistan - Ghufran Adnan; Pirbhat Shams; Maria A. Khan; Jamshed Ali; Nasir Rahman; Fateh Ali Tipoo; Zainab Samad; Saulat Hasnain Fatimi; Saira Bukhari; Osman Faheem (Ubiquity Press, 2021)
Aims: To identify the changes in cardiovascular disease presentation, emergency room triage and inpatient diagnostic and therapeutic pathways. Methods: We conducted a retrospective cohort study at the Aga Khan University Hospital, Karachi. We collected data for patients presenting to the emergency department with cardiovascular symptoms between March-July 2019 (pre-COVID period) and March-July 2020 (COVID period). The comparison was made to quantify the differences in demographics, clinical characteristics, admission, diagnostic and therapeutic procedures, and in-hospital mortality between the two periods. Results: Of 2976 patients presenting with cardiac complaints to the emergency department (ED), 2041(69%) patients presented during the pre-COVID period, and 935 (31%) patients presented during the COVID period. There was significant reduction in acute coronary syndrome (ACS) (8% [95% CI 4-11], p < 0.001) and heart failure (↓6% [95% CI 3-8], p < 0.001). A striking surge was noted in Type II Myocardial injury (↑18% [95% CI 20-15], p < 0.001) during the pandemic. There was reduction in cardiovascular admissions (coronary care unit p < 0.01, coronary step-down unit p = 0.03), cardiovascular imaging (p < 0.001), and procedures (percutaneous coronary intervention p = 0.04 and coronary angiography p = 0.02). No significant difference was noted in mortality (4.7% vs. 3.7%). The percentage of patients presenting from rural areas declined significantly during the COVID period (18% vs. 14%, p = 0.01). In the subgroup analysis of sex, we noticed a falling trend of intervention performed in females during the COVID period (8.2% male vs. 3.3 % female). Conclusions: This study shows a significant decline in patients presenting with Type I myocardial infarction (MI) and a decrease in cardiovascular imaging and procedures during the COVID period. There was a significant increase noted in Type II MI.